Intraoperative Surgical Margin Clearance – Correlation of Touch Imprint Cytology, Frozen Section Diagnosis, and Histopathological Diagnosis - Tamhane, Ankita Narendra (Int J Appl Basic Med Res, 2020)
INTRODUCTION: Touch imprint cytology (TIC) and frozen section diagnosis are valuable intraoperative guides for the management of malignancies as they make a prompt therapeutic decision that may prevent surgical re-intervention. The present study emphasizes on the correlation of TIC and frozen section for the evaluation of surgical margins considering histopathological diagnosis as the gold standard. AIM: The aim of the study was to assess the accuracy of frozen section diagnosis and TIC in the evaluation of surgical margin clearance. MATERIALS AND METHODS: It is a prospective analytical study of 103 patients carried in the histopathology section of department of pathology for 1 year from July 2017 to July 2018. Specimens were received in the frozen section room, grossed by the standard protocol. Touch imprints of margins were taken, and frozen sections were stained by rapid hematoxylin and eosin stain. The same margins were sent for permanent histopathology sections. RESULTS: Of 103 patients, 51 (49.51%) were oral squamous cell carcinoma, 35 (33.98%) carcinoma breast, 9 (8.74%) carcinoma colon, 4 (3.88%) squamous cell carcinoma of skin, 3 (2.91%) basal cell carcinoma, and 1 (0.97%) malignant peripheral nerve sheath tumor. Frozen section diagnosis for margin clearance of the above organs showed that the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were found to be 100%, 98.71%, 100%, 100%, and 99.02%, respectively. The sensitivity, specificity, PPV, NPV, and accuracy of TIC for surgical margin clearance were 46.15%, 100%, 100%, 84.62%, and 86.40%, respectively. CONCLUSION: Frozen section diagnosis is an accurate method for the assessment of surgical margin clearance as compared to TIC. This study evaluated predominantly epithelial malignancies than mesenchymal malignancies, thus emphasizing its utility in it. More research needs to be done for the assessment of the utility of these lesions.